Unknown waters : a firsthand account of the historic under-ice survey of the Siberian continental shelf by USS Queenfish (SSN-651) - McLaren, Alfred Scott (University of Alabama Press, 2008)
Tells the story of the brave officers and crew of the nuclear submarine USS Queenfish (SSN-651), who made the first survey of the remote and important Arctic Ocean region. The unpredictability of floating sea ice, shallow waters, and possible Soviet discovery, all play a dramatic part in this 1970 voyage.